La persistenza di Montesquieu: interpretazioni e letture novecentesche - Galli, Giovanni (Montesquieu.it, 2012)
Montesquieu is widely known as one of the most important and influential authors of the French Enlightenment. The anthology of collected essays reviewed below, Lo spirito della politica. Letture di Montesquieu, edited by Domenico Felice, finds its name from one of the Montesquieu’s books entitled, De l’esprit des lois, written in 1748. Many authors from the twentieth century have studied different issues about Montesquieu’s opus maius. Some of the main arguments they discuss, like the method of his work and its relation with the Aristotelian empirical enterprise, or the differences between the claims of his thinking and that of Rousseau and many other, are now presented inside this collection of essays. It could be a useful guide for those who would like to start the study of Montesquieu’s ideas.